Pharmacological Characterization of Vasorelaxant Effects of BMS-180448, a Novel Cardioselective ATP-Sensitive Potassium Channel Opener, in Rat Aorta - Yang-Su Park; Sung-Eun Yoo; Hwa-Sup Shin; Yong-Ri Jin; Yeo-Pyo Yun (Elsevier, 2003)
This study was designed to characterize vasorelaxant effects of BMS-180448 ((3S-trans)-N-(4-chlorophenyl)-N'-cyano-N"-(6-cyano-3,4-dihydro-3-hydroxy-2,2-dimethyl-2H-1-benzopyran-4-yl)), a prototype cardioselective ATP-sensitive potassium channel opener, in rat aorta. BMS-180448 relaxed phenylephrine-precontracted endothelium-intact aortic rings (IC50: 0.97 ± 0.29 μM), the effect being significantly attenuated by removal of functional endothelium (IC50: 1.95 ± 0.23 μM) and pretreatment with NG-nitro-L-arginine methyl ester (L-NAME) or methylene blue. BMS-180448 completely relaxed endothelium-denuded aorta contracted with phorbol 12,13-dibutyrate, PGF2a, and U46619 with a significantly greater potency (IC50: 0.069 ± 0.002, 0.055 ± 0.002, and 0.068 ± 0.008 μM, respectively, P<0.05) than that contracted with phenylephrine (1.95 ± 0.23 μM) or KCl (0.25 ± 0.08 μM), indicating potency change with the type of vasoconstrictor. BMS-180448 (1 - 3 μM) inhibited Ca2+ (0.5 - 2.5 mM)-induced contraction of endothelium-denuded aorta evoked in the presence of high KCl (65.4 mM), but had no effect on contraction induced by phenylephrine in Ca2+-free buffer. BMS-180448 (10 μM) increased cAMP level in aorta by approximately two-fold compared with the control, comparable to forskolin, an adenylate cyclase activator. These findings suggest that cardioselective BMS-180448 still exerts significant vasorelaxant activity in rat aorta contracted with various vasoconstrictors via multiple mechanisms including the blockade of extracellular Ca2+ influx through voltage-dependent channels and activation of the adenylate cyclase and nitric oxide pathway, with the possibility of hemodynamic implications in certain clinical conditions such as myocardial infarction and hypertension.